Efektivitas Pemberian Air Kelapa Muda (Hijau) Terhadap Lama Kala Ii Pada Ibu Intranatal - Saleng, Hasriani; Ghita, Dwi; Sampara, Nurqalbi; K, Rahayu Eryanti (Madu : Jurnal Kesehatan, 2023)
Prolonged labor is a risk factor for maternal and infant mortality. Labor progresses through four phases, with stage II being the second to last. The administration of young (green) coconut water to intranasal women was investigated to see if it would increase the duration of the second stage. This study aimed to determine whether consuming young coconut water during labor can reduce the length of stage II in intrapartum women. A Quasi-Experimental design with a post-test-only control group was used for this investigation. Thirty-four residents of RSIA Puskesmas bara-baraya were randomly selected and divided into two groups: those given young coconut water and those given a placebo. Of the total 34 respondents, it was determined by Independent T-Test analysis that 16 (47.1%) of the Old Stage II intervention group experienced fast, and 1 (2.9%) experienced slow. In contrast, among those who took the control group survey, the fastest response time was 2.9%, and the slowest was 47.1%. Giving young (green) coconut water to laboring mothers is effective in increasing intranasal maternal strength in long-stage II labor, so it is recommended for health workers to further improve care for laboring mothers by making contractions (labor) effective in non-pharmacological ways.